The Concept of Islamic Education Regarding Ethics in Seeking Knowledge - Besari, Anam (STAI MA'ARIF MAGETAN, INDONESIA, 2023)
An increasingly modern civilization must be balanced with adequate developments in science and technology, so that human civilization can adapt to the needs of the civilization it faces. Because otherwise humans will be increasingly left behind by their own time. Then it really needs the development of education in accordance with the times. This is because education is like a part of civilization itself. However, the development of civilization and the development of education without adequate moral education will be useless and will even add to the depravity of human civilization itself. So it is very important in the current era of moral education. Because only with morals will this human civilization be stable and even better than the previous one. Moral education can be started from the family, the environment, even in education, priority should be given to material and moral practices that are commendable so that students can absorb and practice them directly, so that they will get used to doing good things without coercion.